Case Report: Buccal shifted flap with palatal “C” shape ridge split to facilitate the palatal bone augmentation without compromising the buccal vestibular depth: Report on three cases - Ye, Mingfu; Chen, Zhaozhao; Liu, Wenjun; Wang, Hom-Lay (Frontiers in Bioengineering and Biotechnology, 2025)
Due to its dense connective tissue structure, the coronal advancement of the palatal flap is not feasible, making the reconstruction of single-site palatal bone defects particularly challenging. This case report describes the effectiveness and efficacy of an innovative technique combining the buccal shifted flap and palatal “C”-shaped ridge split together during bone augmentation procedures in the posterior maxilla. The described approach not only facilitates obtaining reliable bone regeneration without compromising the vestibular depth, but also surprisingly increases the horizontal contour.